Determination of thermodynamic functions and structural parameters of NpO2+ lactate complexes - Maiwald, Martin M.; Müller, K.; Heim, K.; Trumm, M.; Banik, N. L.; Rothe, J.; Dardenne, K.; Skerencak-Frech, A.; Panak, Petra (New journal of chemistry, 2020)
The complexation of NpO2+ with lactate in aqueous solution is studied as a function of the total ligand concentration ([Lac−]total), ionic strength (Im = 0.5-4.0 mol kg−1 Na+(Cl−/ClO4−)) and temperature (T = 20-85 °C) by Vis/NIR absorption spectroscopy. The formation of two NpO2+ lactate species with the stoichiometry NpO2(Lac)n1−n (n = 1, 2) is observed at the studied experimental conditions. The temperature dependent conditional stability constants log βj′(T) at different ionic strengths are calculated with the law of mass action. The conditional data are extrapolated to IUPAC reference state conditions (Im = 0) with the specific ion interaction theory (SIT). With increasing temperature up to 85 °C log β01(20 °C) = 1.92 ± 0.14 decreases by 0.12 and log β02(20 °C) = 2.10 ± 0.13 decreases by 0.17. The thermodynamic stability constants correlate linearly with the reciprocal temperature according to the integrated Van’t Hoff equation. Thus, linear regression analyses yield the standard reaction enthalpy ΔrH0 and entropy ΔrS0 for the complexation reactions. In addition, the sum of the SIT specific binary ion-ion interaction coefficients Δεj,k(T) of the complexation reactions are determined by variation of the ionic strength. Structural parameters of the formed complex species and the coordination mode of lactate towards the NpO2+ ion are investigated as a function of pHc by extended X-ray absorption fine structure spectroscopy (EXAFS) and attenuated total reflection Fourier-transform infrared spectroscopy (ATR-FT IR). The results show, that the coordination mode of lactate changes from end-on (coordination via only the COO− group) to side-on (formation of chelate rings involving the OH-group) with increasing pHc. The experiments are supported by quantum chemical calculations.
Im Titel ist die Ziffer 2 tief- und das "+" hochgestellt
Gesehen am 10.06.2021